LE LEGUE DE TINDOUF, UNE IMAGE RETROUVEE QUI RISQUE LE PERIL - BENTALEB Zine El Abidine (My University, 2016)
Cities and historic areas became historical heritage, are facing today many difficulties in relation with their conservation, particularly their use and their inclusion in the contemporary city. With this study, we start with the observation of the phenomenon of degradation of urban and architectural heritage and the need to safeguard it. and we do it through a case study of city of Tindouf (southwestern Algeria) which is an illustrative example of the degraded ancient centers requiring interventions. Due to its history, its location and its geology, the city of Tindouf offers a rich and diverse tangible and intangible heritage. The aim of this study is to consider the built heritage not only in physical and architectural way but rather with a multidimensional vision: historical, cultural and socio-anthropological. The ksourien built heritage is the result of the interaction of all these dimensions in time and in space. After a long process of investigation on field (relevés, surveys, interviews, the archives consultation ...), work has been covered by three different approaches on two ksour which constitute the historic core of Tindouf. First, a typological approach in the French school to better understand the typology of Tindouf’s ksourien architecture. The socio-anthropological approach as a second approach to better understands the lived space and perceived according to residents, for this, the survey and semi-structured interviews were done and analyzed by the method of analysis contained. Finally, our concern is to identify the different needs and strengths of reading and understanding from the information obtained by the analysis performed during the diagnostic period before the rehabilitation action, taking into consideration what conditions the heritage interest and existing urban tensions.
Keywords: Heritage, Ksar, historical center, saving, Tinouf, architectural style, urban tissue